Enhancing the Students’ Critical Thinking Ability and Learning Outcome Through Poe Learning Model - Tri Wahyu Setiyani; Madziatul Churiyah; Moh Arief (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2019)
This study aims to determine the implementation of Predict-Observe-Explain (POE) learning model, enhancing critical thinking and students’ learning outcome on archiving. This research is a classroom action research utilizing qualitative approach consisting of two cycles on students of Office Administration. The subject were students at one of the vocational school in East Java, using data analysis in the form of data reduction, data presentation, and drawing conclusion or verification. The results showed that POE learning model is able to improve students' ability to think on Archiving. The students’ cognitive learning, affective, and psychomotor also increased as the implementation of learning model. Hence, the POE learning model is effectively used in learning.